Pedagogical studies: specificity - condition - problems - perspectives - Dorota Jankowska (Studia z Teorii Wychowania)
My intention is to draw attention to pedagogical studies, and more specifically Pedagogy that according to ISCED-F 2013 classification belong to broad field named Education. The rationale for taking up this subject is the special and requiring reflection situation of pedagogical studies, including its relation to teacher training In my opinion, in Poland pedagogical studies has begun the next stage of its functioning and it will most likely change significantly in the upcoming years. In the article, I argue that the perspective of changes in pedagogical studies is determined not only by the general direction of changes in academic education, but also by following factors:(1) the new situation of pedagogy as a scientific discipline, which is the basis for the analysed field of study, (2) pedagogization of social life, which results in broadening the fields of activity for graduates in pedagogy. The aim of the article is to raise the issue of the specificity of pedagogical studies, to indicateitscurrent condition and to outline both the problems it face and perspectives it has